Feeding effect of total mixed ration on milk yield, nutrient intake, digestibility and rumen environment in Red Chittagong Cows - Sarker, Nathu Ram; Yeasmin, Dilruba; Habib, Md Ahsan; Tabassum, Farah (Asian Journal of Medical and Biological Research, 2019)
Efficient utilization of crop residues is an alternative way to overcome feed shortage for livestock feeding. Hence, an experiment was conducted to determine the effect on nutrient intake, milk yield, nutrient digestibility and rumen parameters of total mixed ration (TMR) as mash or block form in comparison to conventional feeding system for a period of 45 days. Accoding to CRD 18 RCC early milking cows (Bos indicus) having average daily milk yield of 3.20±0.14 L/d and divided into three treatment groups. Existing feeding practice at the farm was considered as control group (T0) fed Napier-3 adlib. and concentrate mixture. In another two groups, animals fed TMR, where one fed as block (T1) and another as mash form (T2) with the same roughage and concentrate combination (50:50). All diets contained 16% CP. To determine digestibility of supplied feed, a digestibility trial at the middle of the feeding trial was conducted and also to study the rumen environment (pH, TVFA, NH3-N), rumen liquors were collected at post feeding intervals of 3, 6, 12, 24 and 36h. Study revealed that fresh feed intakes were significantly (p<0.001) higher in T0. DMI and CPI were significantly (p<0.001) higher in T1 group. Significantly (p<0.05) highest milk yields were obtained in T1 (3.6 l/d) and T2 (3.49 l/d) and lowest in T0 (3.35l/d). Milk fat (p<0.001) and SNF (p<0.05) were significantly higher T1 and T2. Except ADF, digestibility for most of the nutrient was significantly higher in T1 and T2 than T0. Total volatile fatty acids (TVFA) and ammonia-nitrogen (NH3-N) were significantly (p<0.01) higher in T1 and T2 groups than that of T0 group. Finally, it may be concluded that TMR, either in block or mash form gives better results in terms of milk yield, milk composition, digestibility and concentration of TVFA and NH3-N. Asian J. Med. Biol. Res. March 2019, 5(1): 71-77